2019
DOI: 10.1111/1365-2656.13059
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft sound exposure leads to song frequency decline and elevated aggression in wild chiffchaffs

Abstract: The ubiquitous anthropogenic low‐frequency noise impedes communication by masking animal signals. To overcome this communication barrier, animals may increase the frequency, amplitude and delivery rate of their acoustic signals, making them more easily heard. However, a direct impact of intermittent, high‐level aircraft noise on birds’ behaviour living close to a runway has not been studied in detail. We recorded common chiffchaffs Phylloscopus collybita songs near two airports and nearby control areas, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 69 publications
(107 reference statements)
1
21
1
Order By: Relevance
“…Singing earlier or singing less may also make birds more vulnerable to territorial intrusions and may force individuals into physical fight more often, which may bring risk of injury and increased chance of predation. This matches well with a pattern of noise-dependent aggression levels (Slabbekoorn, 2013), for which there is growing evidence from birds in cities (Phillips and Derryberry, 2018) and around airports (Wolfenden et al, 2019). Lower song activity during noisy daytime conditions, as found in our study, also matches with noise-induced rise in vigilance and distraction, which has been shown to reduce foraging efficiency (Quinn et al, 2006;Campbell et al, 2019).…”
Section: Causes and Consequencessupporting
confidence: 90%
“…Singing earlier or singing less may also make birds more vulnerable to territorial intrusions and may force individuals into physical fight more often, which may bring risk of injury and increased chance of predation. This matches well with a pattern of noise-dependent aggression levels (Slabbekoorn, 2013), for which there is growing evidence from birds in cities (Phillips and Derryberry, 2018) and around airports (Wolfenden et al, 2019). Lower song activity during noisy daytime conditions, as found in our study, also matches with noise-induced rise in vigilance and distraction, which has been shown to reduce foraging efficiency (Quinn et al, 2006;Campbell et al, 2019).…”
Section: Causes and Consequencessupporting
confidence: 90%
“…2016, Wolfenden et al . 2019), in an attempt either to overcome noise disrupting environmental cues (‘masking’, Lohr et al . 2003) or to draw attention to a potential threat (risk perception, Halfwerk et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on past noise research, we predicted species richness would decline because part of the bird community would respond by decreasing vocalizations in the presence of aircraft noise (Francis et al 2009, Proppe et al 2013, McClure et al 2013, Manzanares Mena & Mac ıas Garcia 2018. However, some bird species have demonstrated a heightened vocalization response to noise due to masking or risk perception (Potash 1972, Brumm 2004, Patricelli & Blickley 2006, D ıaz et al 2011, R ıos-Chel en et al 2012, Dominoni et al 2016, Wolfenden et al 2019, in an attempt either to overcome noise disrupting environmental cues ('masking', Lohr et al 2003) or to draw attention to a potential threat (Table 1) on observed vocal richness by minute when numerical and categorical terms were held at their median and mode, respectively (n = 520). The points are raw richness count data for each minute sampled, the horizontal bars are model-derived species richness estimates and the shaded areas represent 95% confidence intervals.…”
Section: Site Differences In Response To Aircraftmentioning
confidence: 99%
See 1 more Smart Citation
“…Although road traffic noise is probably the most prevalent source of noise of human origin, airports represent another interesting scenario to address the impact of noise pollution on wildlife. Since aircraft noise is one of the loudest and most disturbing sounds experienced by humans (Pepper et al 2003), with aircrafts reaching peaks of > 110 dB, wildlife living nearby airports could also be suffering from the exposure to chronic bursts of aircraft noise (Wolfenden et al 2019). Empirical work in rats and humans has shown that aircraft noise is capable of raising oxidative stress levels (Kröller-Schön et al 2018), molecules related to stress (e.g.…”
Section: Introductionmentioning
confidence: 99%